2020
DOI: 10.1038/s41598-020-64026-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and biological activities of in vitro cultured Nidularium procerum, a bromeliad vulnerable to extinction

Abstract: In this study, Response surface methodology (RSM) was applied to optimize the yield of crude methanolic extract of Mitragyna speciosa leaves using Ultrasound-assisted extraction (UAE). The crude methanolic extract and its fractions were quanti ed in terms of total phenolic content and total avonoid content, along with characterized using Fourier-transform infrared and Gas chromatography-mass spectrometry. The results showed the maximum yield of 49.72% at the optimal conditions (temperature, 34 °C; time, 25 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…This study showed that the hydroethanolic extracts of Alstonia boonei and Carica papaya contain alkaloids, flavonoids, phenolics, tannins, saponins, anthraquinones, and terpenoids ( Table 1 ). Alkaloids, flavonoids, and tannins are known for their antioxidant, antimalarial, antimicrobial, anticancer, and anti-inflammatory activities [ 27 , 28 ]. The extracts had total phenolics (34.13 ± 1.90 mg GAE/g for Alstonia boonei and 27.99 ± 1.46 mg GAE/g for Carica papaya ) and total flavonoid (19.47 ± 1.89 mg QE/g for Alstonia boonei and 18.24 ± 1.36 mg QE/g for Carica papaya ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the hydroethanolic extracts of Alstonia boonei and Carica papaya contain alkaloids, flavonoids, phenolics, tannins, saponins, anthraquinones, and terpenoids ( Table 1 ). Alkaloids, flavonoids, and tannins are known for their antioxidant, antimalarial, antimicrobial, anticancer, and anti-inflammatory activities [ 27 , 28 ]. The extracts had total phenolics (34.13 ± 1.90 mg GAE/g for Alstonia boonei and 27.99 ± 1.46 mg GAE/g for Carica papaya ) and total flavonoid (19.47 ± 1.89 mg QE/g for Alstonia boonei and 18.24 ± 1.36 mg QE/g for Carica papaya ).…”
Section: Resultsmentioning
confidence: 99%
“…e extracts had a significant chemosuppressive and curative antimalarial effect on the infected mice when compared with the untreated group. is is believed to be as a result of some of the bioactive compounds such as flavonoids, phenolics, alkaloids, and anthraquinones present in the extracts [27][28][29]. e extracts reduced parasitemia and increased mean survival time in the treated group.…”
Section: Resultsmentioning
confidence: 99%
“…Fenugreek extract @ 25% has proved to be significant for inhibiting fungal radial growth, this could be due to biologically active constituents of T. foenum-graecum (Haouala et al, 2011). The application of fenugreek extract lowered the disease severity under both greenhouse and field conditions, which could be attributed to presence of secondary metabolites i.e., phenolic compounds, flavonoids, tannins and coumarins (Gollo et al, 2020). Fenugreek extract has certain allelochemicals i.e., kaempferol, kaempferol-glucoside and β-d-glucopyranoside (Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Two drops of concentrated HCl (37%, MerckMillipore, Darmstadt, Germany) were added followed by a chip of magnesium metal. Appearance of a magenta color indicated the presence of flavonoids (Akter et al, 2016;Suurbaar et al, 2017;Gollo et al, 2020).…”
Section: Flavonoids Identificationmentioning
confidence: 99%